2007
DOI: 10.5194/acp-7-3385-2007
|View full text |Cite
|
Sign up to set email alerts
|

Including the sub-grid scale plume rise of vegetation fires in low resolution atmospheric transport models

Abstract: Abstract. We describe and begin to evaluate a parameterization to include the vertical transport of hot gases and particles emitted from biomass burning in low resolution atmosphericchemistry transport models. This sub-grid transport mechanism is simulated by embedding a 1-D cloud-resolving model with appropriate lower boundary conditions in each column of the 3-D host model. Through assimilation of remote sensing fire products, we recognize which columns have fires. Using a land use dataset appropriate fire p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
501
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(507 citation statements)
references
References 52 publications
6
501
0
Order By: Relevance
“…The remaining 75 % of the emissions are distributed from the surface to the PBL height with constant mass mixing ratio. Vertical emission distributions with constant mass mixing ratios have been used in most former global aerosol modeling studies even in case of more advanced plume models, e.g., Freitas et al (2007). Our knowledge about the global variability of vertical emission distributions is even more limited than our knowledge about the plume heights.…”
Section: Vertical Distribution Of Wildfire Emissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 75 % of the emissions are distributed from the surface to the PBL height with constant mass mixing ratio. Vertical emission distributions with constant mass mixing ratios have been used in most former global aerosol modeling studies even in case of more advanced plume models, e.g., Freitas et al (2007). Our knowledge about the global variability of vertical emission distributions is even more limited than our knowledge about the plume heights.…”
Section: Vertical Distribution Of Wildfire Emissionsmentioning
confidence: 99%
“…Overall, modeling as well as observational studies (e.g., Diner et al, 2008;Val Martin et al, 2010;Ichoku et al, 2012) indicate that wildfire plume heights are highly variable on the global scale. While Freitas et al (2007), Rio et al (2010) and others demonstrated a reasonable performance for their specific plume height parametrizations in particular case studies; other authors including Val Martin et al (2012) and Goodrick et al (2012) presented results that showed a poor to moderate performance of all these models on the global scale.…”
Section: A Veira Et Al: Impact On Transport Black Carbon Concentramentioning
confidence: 99%
See 2 more Smart Citations
“…Smoke injection heights are key inputs for aerosol transport modeling, as they are critical for determining the distance and direction of the travelling smoke (e.g., Colarco et al, 2004;Freitas et al, 2007). Biomass burning emits hot gases and particles, which are transported upward due to positive buoyancy.…”
Section: Introductionmentioning
confidence: 99%